1996
DOI: 10.1111/j.1476-5381.1996.tb15521.x
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of human nasal airway responses to bradykinin and histamine by inhibitors of nitric oxide synthase

Abstract: 1 The effects of inhibitors of nitric oxide synthase and local anaesthetics were studied on changes in human nasal airway patency and albumin extravasation in response to bradykinin and histamine, in vivo. 2 Compared with the action of the vasoconstrictor, ephedrine, 2.5 ,umol, N0-nitro-L-arginine methyl ester (L-NAME), 1 pmol alone, did not change the resting value of the minimal cross-sectional area (A min) of the human nasal airway. L-NAME, 0.1 to 10 ymol, produced a dose-related inhibition of the reduction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 20 publications
2
22
1
Order By: Relevance
“…Based upon the present study's result and a report that L-NAME did not change nasal airway resistance from baseline in healthy subjects (28), NO may not substantially act as a vasodilator in nasal airways under unstimulated conditions.…”
Section: Discussionsupporting
confidence: 63%
“…Based upon the present study's result and a report that L-NAME did not change nasal airway resistance from baseline in healthy subjects (28), NO may not substantially act as a vasodilator in nasal airways under unstimulated conditions.…”
Section: Discussionsupporting
confidence: 63%
“…Histamine exerts its inflammatory effects, in part, through NO generation in situ [35], since the blockade of NOS significantly inhibited histamine-induced plasma extravasation in human nasal airway [42]. Interestingly, Ali and co-workers [43] demonstrated that low concentration of H2S or spontaneous H2S donors reversed histamine, but not isoprenaline-induced vasodilatation, possibly via a direct chemical reaction between H2S and NO, which may lead to the formation of a nitrosothiol [44] or even nitroxyl species (NO-/HNO) [45] of poor vasorelaxant activities.…”
Section: Discussionmentioning
confidence: 99%
“…To study whether the response to ACh was nitric oxide (NO)-dependent, a cumulative concentration-response curve was determined after the tissue was incubated for 30 min with either: the vehicle; nitro-L-arginine-methyl-ester (L-NAME; an NO synthase (NOS) inhibitor) alone; or L-NAME in combination with L-arginine (a NOS substrate) [11,12]. The concentration of L-NAME (1610 -5 M) used was found to be effective in inhibiting the relaxation induced by calcium ionophore A23187 (1610 -9 -1610 -3 M) in PE-pre-contracted vascular segments.…”
Section: Methodsmentioning
confidence: 99%